2013
DOI: 10.1371/journal.pone.0086266
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trichomonas vaginalis and Cytological Abnormalities of the Cervix in Low Risk Women

Abstract: ObjectiveIs Trichomonas vaginalis (TV) an inducing factor for the development of (pre-)cancerous lesions of the cervix?DesignCross sectional study.SettingScreening healthy Belgian women with low infection risk.Sample63,251 consecutive liquid based cervical samples.MethodsReal time quantitative PCR for presence of TV, 18 HPV types and Pap smear analysis of cytologic abnormalities. Main Outcome MeasuresAssociation of TV and HPV with cervix dysplasiaResultsThe overall prevalence of TV DNA was 0.37%, of low risk H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 25 publications
3
50
1
3
Order By: Relevance
“…Lazenby et al [27] discovered more than sixfold higher risk of women with TV being infected with HPV type 16 infection. We saw an association of TV with ASCUS and LSIL which was similar to the findings of a Belgian study where such associations were seen among women with high-risk HPV infection [28]. Depuydt et al [29] in their study done in Antwerp also demonstrated a higher association between TV and HPV infections.…”
Section: Discussionsupporting
confidence: 88%
“…Lazenby et al [27] discovered more than sixfold higher risk of women with TV being infected with HPV type 16 infection. We saw an association of TV with ASCUS and LSIL which was similar to the findings of a Belgian study where such associations were seen among women with high-risk HPV infection [28]. Depuydt et al [29] in their study done in Antwerp also demonstrated a higher association between TV and HPV infections.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, the finding of TV showed statistical significance for the ASC-H group. Another study found an association between ASC-US and these vaginal protozoa when comparing LBC results (SurePath ® ) and using real-time PCR for TV, but no cases of ASC-H were reported with this pathogen [11] . This discrepancy in the results can be explained by the more sensitive method used in that study, as well as the different populations examined.…”
Section: Discussionmentioning
confidence: 99%
“…Cervicovaginal infections are common in women and cause uncomfortable symptoms, such as vaginal discharge, odor, and pruritus [9,10] . Concomitant infections by multiple microorganisms are also common, and they may have symbiotic interactions [11] . Some of these pathogens can infect the female genital mucosa and induce cytological atypia [12] .…”
Section: Introductionmentioning
confidence: 99%
“…To date, tests like the APTIMA or BD affirm VPIII T. vaginalis assays have proven to be sensitive and specific [41][42][43][44][45], but they are not yet widely available, applied and cost-effective for many settings. Still, T. vaginalis is a silent danger, that is, in many settings, more prevalent and endemic than previously understood, it has been associated with pelvic in-flammatory disease and adverse outcomes of pregnancy (low birth weight and premature birth), and that can also disturb the cytological diagnosis of cervix smears [46]. Moreover, T. vaginalis increases the risk to acquire and transmit several other STIs including HIV [47][48][49], and it may spread to sexual partners because they are not aware of its presence.…”
Section: Nucleic Acid Amplifications Tests and Point-of-carementioning
confidence: 99%